Perspectives and Functions of Music in Role Art - Wiflihani Wiflihani; Raden Burhan Surya Natad; Mei Sonni Sinaga; Frisdo Ekardo (Budapest International Research and Critics University, 2022)
Music is basically a work of art that was born from a thought or idea from a composer through a process of artistic creativity on a work that was created. Music has many important functions in the art world, one of which is acting. Among them are building and strengthening the emotions of characters in acting. In addition, music is also needed as an atmosphere amplifier so that it can stimulate the imagination and become the center of attention of the audience. Music aims to enter into the emotions of the actor and the audience and then be able to influence the knowledge of the actor and the audience itself in the form of behavior as a result of the music they listen to. Music is more influential in the context of expression. Apart from being an aura art, music also gives a feeling of life to the body of the cast. The problem is how the meeting of